1987
DOI: 10.2134/agronj1987.00021962007900010014x
|View full text |Cite
|
Sign up to set email alerts
|

Mefluidide Applications for Annual Bluegrass Seedhead Suppression Based on Degree‐Day Accumulation1

Abstract: Mefluidide [N‐(2,4‐dimethyl‐5‐{[(trifluoromethyl)sulfonyl] amino}phenyl) acetamide] is an effective growth regulator for annual bluegrass [Poa annua var. reptans (Hauskins) Timm.] seedhead suppression. The effectiveness of mefluidide is dependent on the rate and timing of application. The objective of this field study was to determine the lowest effective rate and the proper time for mefluidide application based on growing degree‐days (GDD). Soil types were a fine, mixed, mesic Aeric Ochraqualf and fine‐loamy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 2 publications
0
27
0
Order By: Relevance
“…Ong and Marshall (1975) found that assimilate redistribution to ABG roots increased when developing seedheads were physically removed compared to where seedheads were allowed to mature. Mefluidide limits seedhead production of ABG (Danneberger et al, 1987) and it provided the greatest control of seedheads in our study. Several studies have shown that application of ME re‐allocates photosynthate away from shoots and seedheads to root and crown tissues (Cooper et al, 1987, 1988; Hanson and Branham, 1987).…”
Section: Discussionmentioning
confidence: 67%
“…Ong and Marshall (1975) found that assimilate redistribution to ABG roots increased when developing seedheads were physically removed compared to where seedheads were allowed to mature. Mefluidide limits seedhead production of ABG (Danneberger et al, 1987) and it provided the greatest control of seedheads in our study. Several studies have shown that application of ME re‐allocates photosynthate away from shoots and seedheads to root and crown tissues (Cooper et al, 1987, 1988; Hanson and Branham, 1987).…”
Section: Discussionmentioning
confidence: 67%
“…GDD models have been shown to accurately predict the growth of various cereals and grasses (6,10,16,20,23,25,26,28,38). Additionally, GDD models have been used to maximize the efficacy of insecticide (36) and plant growth regulator (7,13) applications to managed turfgrass systems.…”
Section: Growing Degree Day Modelingmentioning
confidence: 99%
“…In the current study, ME probably did not sufficiently inhibit seedhead production (only 12 to 15% reduction) to adequately divert photosynthate from the developing inflorescence (27) to improve root growth and reduce disease. Timing of ME application can influence seedhead suppression (9). Danneberger et al (9) evaluated annual bluegrass seedhead suppression with ME applications based on growing degree days.…”
Section: Discussion Of Plant Growth Regulator Effects On Anthracnose mentioning
confidence: 99%
“…Timing of ME application can influence seedhead suppression (9). Danneberger et al (9) evaluated annual bluegrass seedhead suppression with ME applications based on growing degree days. They observed that ME applications at 25 and 30 accumulated growing degree days (base 32°F beginning 1 April) provided the greatest seedhead suppression; whereas ME applied at 15 and 45 degree days was less effective.…”
Section: Discussion Of Plant Growth Regulator Effects On Anthracnose mentioning
confidence: 99%